Gene Regulation by p53 in Human Cancer System - Ghosh, Supratit; Bhattacharjee, Meghna; Jana, Nandan Kumar (Asian Pacific Journal of Cancer Biology, 2022)
TP53 proto-oncogene constitutes tumor induction in more than 50% of human cancers as it is mutated frequently in a wide range of cell lines. The transcription of TP53 is postulated to be autoregulated via either binding with TBP and CBF or via direct interaction of p53 protein with TP53 promoter, though further investigation is needed to acknowledge it. Alteration in pathways, regulated through wild type, by mutant p53 (Mutp53) give rise to immortality through interaction with other transcription factors or inducing receptor tyrosine kinases and other signal components. The missense mutation is more frequent constituting more than 60% among all mainly because of the high rate of G>A or C>T transitions in TP53, giving rise to mutation hotspots in R248, R273, etc. In addition to the loss of function, mutations in the TP53 gene also confers oncogenic functions that are not found in wild type p53, referred to as Gain of Function (GOF). GOF mutp53 has been found to promote metastasis, cell proliferation, cell stemness, metabolic reprogramming as well as chemoresistance. Mutp53 also inhibits the wild type effect that is referred to as the Dominant negative effect (DNE). Understanding the mechanisms behind GOF activities, how they promote chemoresistance, and targeting mutp53 will help in improving the treatment of many human cancers with TP53 mutations.